Bone Mineral Loss and Fracture in Sarcoidosis: A Systematic Review and Meta-Analysis - Wai Chung YONG; Sikarin UPALA; Anawin SANGUANKEO (Archives of Rheumatology, 2019)
Objectives: This meta-analysis aims to investigate the possibility of bone mineral loss and fracture in sarcoidosis. Materials and methods: A comprehensive search of the MEDLINE and Embase databases was performed from inception through August 2017. The inclusion criterion was observational studies evaluating the association between sarcoidosis and bone mineral density (BMD) or fracture. The pooled odds ratio (OR) of fracture, standardized mean difference (SMD) of volumetric BMD and areal BMD, and their 95% confidence interval (CI) were calculated using a random-effects meta-analysis to compare risk between sarcoidosis and controls. The between-study heterogeneity of effect-size was quantified using the Q statistic and I2. Results: Data were extracted from 10 studies involving a total of 6,448 sarcoidosis patients and 77,857 controls. The pooled result demonstrated no significant increased risk of fracture in sarcoidosis patients compared with controls (OR=1.68; 95% CI: 0.85-3.31, p value=0.14, I2=72%). There were no differences between the patients and controls in areal BMD (SMD= 0.21 g/cm2; 95% CI: -0.12-0.54, p value= 0.22, I2=0%) or volumetric BMD (SMD= 0.04 mg/cm3; 95% CI: -0.51-0.58, p value=0.89, I2=83%). Conclusion: Our study has not shown an increased risk of fracture or bone mineral loss in sarcoidosis. However, based on the currently available studies with heterogeneity in between, the conclusion for the osteoporosis screening and fracture risk assessment of patients with sarcoidosis cannot be drawn until more studies are available.